Comparison of protective and curative potential of Daucus carota root extract on renal ischemia reperfusion injury in rats. (July 2013) - Afzal, Muhammad; Kazmi, Imran; Kaur, Rupinder; Ahmad, Aftab; Pravez, Mohammad; Anwar, Firoz
Abstract Context: Daucus carota Linn (Apiaceae), a useful vegetable, is traditionally used in treating kidney and hepatic dysfunctions. Objective: To evaluate the protective and curative potential of D. carota root extract on renal ischemia reperfusion injury in rats. Materials and methods: Wistar rats were selected with 8 + 8 groups (n = 6). Renal pedicles of rats were occluded for 45 min and allowed for reperfusion period. In protective and curative studies, 14 days prior and 14 days after the induction of ischemia/reperfusion (I/R), rats received petroleum ether extract (PEE 250 and 500 mg/kg), fractional methanol extract (FME 250 and 500 mg/kg) and direct methanol extract (DME 250 and 500 mg/kg) of Daucus carota root, orally, once daily. Results: PEE at a dose of 500 mg/kg significantly (p < 0.001) reduced the levels of serum creatinine (0.853–3.090 mg/dl), uric acid (1.300–3.500 mg/dl) and urea (58.26–132.00 mg/dl) compared to disease control. FME at a dose of 500 mg/kg body weight significantly (p < 0.001) reduced the levels of serum creatinine (0.960–3.090 mg/dl), uric acid (1.700–3.500 mg/dl) and urea (77.17–132.00 mg/dl) compared to disease control. DME at a dose of 500 mg/kg body weight significantly (p < 0.001) reduced the levels of serum creatinine (1.173–3.090 mg/dl), uric acid (2.267–3.500 mg/dl) and urea (84.75–132.00 mg/dl) compared to disease control. Discussion and conclusion: Findings demonstrate that postconditioning with the D. carota root extract significantly improves kidney function in I/R rats.